Removal of lead, mercury and nickel using the yeast Saccharomyces cerevisiae - Cherlys Infante J (Revista MVZ Córdoba, 2014)
Objective. In this study the biomass of the yeast Saccharomyces cerevisiae was used to remove lead, mercury and nickel in the form of ions dissolved in water. Materials and methods. Synthetic solutions were prepared containing the three heavy metals, which were put in contact with viable microorganisms at different conditions of pH, temperature, aeration and agitation. Results. Both individual variables and the interaction effects influenced the biosorption process. Throughout the experimental framework it was observed that the biomass of Saccharomyces cerevisiae removed a higher percentage of lead (86.4%) as compared to mercury and nickel (69.7 and 47.8% respectively). When the pH was set at a value of 5 the effect was positive for all three metals. Conclusions. pH was the variable that had a greater influence on the biosorption of lead on the biomass of Saccharomyces cerevisiae. The affinity of the heavy metals for the biomass followed the order Pb>Hg>Ni.